Efficacy of atomoxetine versus midodrine for neurogenic orthostatic hypotension. Issue 1 (19th December 2019) - Byun, Jung‐Ick; Kim, Do‐Yong; Moon, Jangsup; Shin, Hye-Rim; Sunwoo, Jun‐Sang; Lee, Woo‐Jin; Lee, Han‐Sang; Park, Kyung‐Il; Lee, Soon‐Tae; Jung, Keun‐Hwa; Jung, Ki‐Young; Kim, Manho; et al.
Abstract: Objective: The efficacy and safety of 1‐month atomoxetine and midodrine therapies were compared. Three‐month atomoxetine and combination therapies were investigated for additional benefits. Methods: This prospective open‐label randomized trial included 50 patients with symptomatic neurogenic orthostatic hypotension (nOH). The patients received either atomoxetine 18 mg daily or midodrine 5 mg twice daily and were evaluated 1 and 3 months later. Those who still met the criteria for nOH at 1 month received both midodrine and atomoxetine for an additional 2 months, and if not, they continued their initial medication. The primary outcome was an improvement in orthostatic blood pressure (BP) drop (maximum BP change from supine to 3 min after standing) at 1 month. The secondary endpoints were symptom scores, percentage of patients with nOH at 1 and 3 months. Results: Patients with midodrine or atomoxetine treatment showed comparative improvement in the orthostatic BP drop, and overall only 26.2% of the patients had nOH at 1 month, which was similar between the treatment groups. Only atomoxetine resulted in significant symptomatic improvements at 1 month. For those without nOH at 1 month, there was additional symptomatic improvement at 3 months with their initial medication. For those with nOH at 1 month, the combination treatment resulted in no additional improvement. Mild‐to‐moderate adverse events were reported by 11.6% of the patients. Interpretation: One‐month atomoxetine treatment was effective and safe in nOH patients. Atomoxetine improved orthostatic BP changes as much as midodrine and was better in terms of ameliorating nOH symptoms.